Development of Corporate Governance in Lithuania - Bivainis, Juozas (Ekonomika, 2000)
This paper provides the research of corporate governance mechanisms in Lithuania together with their legal and regulatory underpinnings. Building proper corporate governance is interpreted as an integral part of developing a sound private sector basis for economic growth of country. Public and private sector decision-makers have attach great importance to issues, such as property protection, and rights and responsibilities of different participants in the governance of corporation. This interest arises from a broader concern for efficient allocation of resources and the development of capital markets.